Marine Debris: The Unseen Struggle of Similajau National Park's Beaches - Siti Aishah, Azhar; Farah Afiqah, Abdullah; Nur Asriza, Azmi; Ruhana, Hassan (UNIMAS Publisher, 2025)
Nestled along the stunning coastline of Sarawak, Malaysia, Similajau National Park is a biodiversity hotspot and a vital sanctuary for sea turtles. Similajau’s Golden Shores and the Guardians of Biodiversity is a comprehensive exploration of this unique ecosystem, offering a multidisciplinary perspective on its ecological significance, conservation challenges, and the intricate relationships between its flora, fauna, and human communities. This groundbreaking work begins with an introduction to Similajau National Park, setting the stage for an in-depth examination of its geophysical and magnetic characteristics, which influence the nesting behaviors of sea turtles. Discover the secrets hidden in the sand as the book delves into the lives of Similajau’s turtles, their nesting habits, and the critical role of coastal vegetation in providing shade and protection for their eggs. The book also addresses pressing environmental issues, such as the impact of marine debris on turtle nesting beaches and the challenges posed by declining water quality in the park’s coastal areas. It explores the density of estuarine crocodiles in Sungai Likau, the diversity of plankton, and the indirect influence of soil fertility on the surrounding ecosystem. Beyond turtles, the book highlights the park’s rich biodiversity, including rapid assessments of potential medicinal plants, primates, and invertebrates, using cutting-edge techniques like environmental DNA (eDNA). It also examines the perceptions of the Bintulu community toward ecotourism, emphasizing the importance of balancing conservation with sustainable development. Rich with scientific insights, vivid imagery, and compelling narratives, Similajau’s Golden Shores and the Guardians of Biodiversity is an essential resource for ecologists, conservationists, and nature enthusiasts. It is both a call to action and a celebration of one of Southeast Asia’s most treasured natural wonders, offering hope and guidance for the preservation of these fragile ecosystems for generations to come.